Emission-line diagnostics for IMBHs in Dwarf Galaxies: accounting for black hole seeding and ultraluminous x-ray source excitation - Richardson, Chris; Wels, Jordan; Garofali, Kristen; Levanti, Julianna M.; Lebouteiller, Vianney; Lehmer, Bret; Basu-Zych, Antara; Berg, Danielle; Bellovary, Jillian M.; Chisholm, John; Kannappan, Sheila J.; Lambrides, Erini; et al. (The astrophysical journal, 2025)
Dwarf active galactic nuclei (AGN) serve as the ideal systems for identifying intermediate-mass black holes (IMBHs) down to the most elusive regimes (∼103-104M⊙). However, the ubiquitously metal-poor nature of dwarf galaxies gives rise to ultraluminous X-ray sources (ULXs) that can mimic the spectral signatures of IMBH excitation. We present a novel photoionization model suite that simultaneously incorporates IMBHs and ULXs in a metal-poor, highly star-forming environment. We account for changes in MBH according to formation seeding channels and metallicity, and changes in ULX populations with poststarburst age and metallicity. We find that broadband X-rays and UV emission lines are insensitive to MBH and largely unable to distinguish between ULXs and IMBHs. Many optical diagnostic diagrams cannot correctly identify dwarf AGN. The notable exceptions include He II λ4686 and [O I] λ6300, for which we redefine typical demarcations to account for ULX contributions. Emission lines in the mid-IR show the most promise in separating stellar, ULX, IMBH, and shock excitation while presenting sensitivity to MBH and fAGN. Overall, our results expose the potential biases in identifying and characterizing dwarf AGN purely on strong-line ratios and diagnostic diagrams rather than holistically evaluating the entire spectrum. As a proof of concept, we argue that recently discovered overmassive black holes (BHs) in high-z JWST AGN might not represent the overall BH population, with many galaxies in these samples potentially being falsely classified as purely star forming.